The Role of Carbon Taxes in Reducing Greenhouse Gas Emissions - Nar, Mehmet (International Journal of Energy Economics and Policy, 2020)
An abnormal rise in greenhouse gases in the atmosphere has triggered a range of environmental problems the foremost of which is global warming. CO2 is among the gases most responsible for the greenhouse effect. That is why, after the 1990s, new tax regimes, also known as energy-carbon taxes, were put in place in an attempt to lower emissions. There is still an ongoing discussion as to whether tax regimes are working in practice. Certain studies have indicated that carbon taxes are effective or partially effective in preventing CO2 emissions. However, others assert that there is no causal relationship between carbon taxes and the lowering of greenhouse gas emissions. In this study, the annual data of 36 OECD countries in the period of 1990-2018 were used. To detect whether a carbon tax is effective in reducing greenhouse gas emissions, the panel data analysis method was employed. The results of the analysis revealed that carbon taxes have no effect on greenhouse gas emissions. Keywords: Carbon Taxes, Greenhouse Gas Emissions, Energy Taxes, Externalities JEL Classifications: P2, O13, H23 DOI: https://doi.org/10.32479/ijeep.10721